Komunikasi Partisipatif Pada Program Pos Pemberdayaan Keluarga (Studi Kasus di RW 05 Kelurahan Situgede, Kecamatan Bogor Barat, Kota Bogor) - I Satriani; P Muljono; R.W.E. Lumintang (Jurnal Komunikasi Pembangunan, 2011)
ABSTRACT Empowerment occurred if individuals or communities were assigned to discuss their daily need, especially in education and health matter. And also the topics were focused in political and economic issues. Empowerment program in alleviating poverty and improving the quality of human resources, promoted by Center for Human Resources Development (P2SDM), LPPM IPB, cooperated with Damandiri Post  Family Empowerment (Posdaya) program. This particular cooperation leading to develop Posdaya poverty community at different level, such were village, hamlet and RW. The objectives of study were: to analyze the role of companion, community leader in Posdaya activities, the participatory communication and its impact to community as well. The research was a constructivist paradigm, located in RW 05 Situgede village, West Bogor, Bogor. The research was conducted in April May, 2011. The study result was the P2SDM-IPB companion as well as consultant task always coodinated by Posdaya Kenanga. The Situgede village, especially RW 05 had several ultimate tasks, included: cadres supervising, training and motivating. Internal involvement Posdaya Kenanga leaders were: providing insight, advice, criticism and building ideas for sustainability activities. The participatory communication occurred in Posdaya Kenanga were: access, heteroglasia, poliponi, dialogue and carnival. Benefit of cadres were: information and knowledge sharing, problem solving and familiarity relationship. Refers to participatory communication among cadres, they could work optimally as well as equaly right to submit opinions, suggestions, and criticism. As a result, their responsibility increased. Keywords: participatory communication, empowerment, cadres.